Using tyrosinase as a monophenol monooxygenase: A combined strategy for effective inhibition of melanin formation. Issue 4 (10th November 2015) - Lee, Sang‐Hyuk; Baek, Kiheon; Lee, Ju‐Eun; Kim, Byung‐Gee
ABSTRACT: Tyrosinase is a binuclear copper‐containing metalloprotein that leads the fast and regio‐selective o ‐hydroxylation of monophenols to o ‐diphenols. However, the subsequent second oxidation to produce o ‐quinones, i.e., melanin precursors, from the o ‐diphenols has restricted its use to the production of functional o ‐diphenol derivatives. Herein, we present a combined strategy for the effective inhibition of melanin formation in tyrosinase reaction, which allows the use of tyrosinase as a monophenol monooxygenase. The o ‐diphenolic products were protected from being oxidized in the tyrosinase reaction by borate ions and L‐ascorbic acid (LAA). Borate‐ o ‐diphenol complexes were favorable formed at high pH and consequentially protected the o ‐diphenolic products from the catecholase activity of tyrosinase. LAA not only directly reduced the byproduct, o ‐quinones, into o ‐diphenols but also assisted the completion of the tyrosinase reaction cycle by removing a hydroxyl group attached to the copper metal cluster at the active site of the met ‐form tyrosinase. The regio‐selective o ‐hydroxylation of 7, 4'‐dihydroxyisoflavone (daidzein) to produce 7, 3', 4'‐trihydroxyisoflavone (3'‐ODI) was successfully carried out by whole E. coli cell biotransformation with heterologously expressed tyrosinase from Bacillus megaterium . The yield of this o ‐hydroxylation of 5 mM daidzein in one‐pot 400 mL reaction was ca. 100% in 90 min and the productivity was 16.3 mg 3'‐ODI · L −1  ·  h −1  ·  DCW mg −1, which is considerably higher than that of other monooxygenases. The method effectively abolished melanin synthesis, so that the o ‐diphenolic product remained stable without enzyme inactivation. Other monophenolic phytochemicals such as resveratrol and genistein could be subjected to the same strategy. After 1 h, 1 mM of genistein and resveratrol were both converted to orobol and piceatannol, respectively, with ca. 95% conversion yield. These results support the strong potential of tyrosinase as a monooxygenase for regio‐selective o ‐hydroxylation of various monophenolic compounds. Biotechnol. Bioeng. 2016;113: 735–743. © 2015 Wiley Periodicals, Inc. Abstract : Herein, the authors present a combined strategy for the effective inhibition of melanin by‐product formation in tyrosinase reaction. The yield of this o ‐hydroxylation of 5 mM daidzein in one‐pot 400 mL reaction was ca. 100% in 90 min and the productivity was 16.3 mg 3′‐ODI· L −1  · h −1  · DCW mg −1, which is considerably higher than that of other monooxygenases. Furthermore, the solubility difference depending on pH allowed an easy purification of product from the reaction mixture.